Inter-American destiny in Guillermo Verdecchia's fronteras Americanas - M. Cristian Réka (Acta hispanica, 2023)
The article scrutinizes the issue of inter-American destiny in the dramatic world of the Argentinian-born Guillermo Verdecchia (b. 1962), whose work was awarded with the prestigious Governor General’s Literary Award (est. 1937) in Canada. Verdecchia deals with a subjective cultural history that shapes various destinies through an inter-American space and given time periods. The thespian plot in his Fronteras Americanas (1993) is an idiosyncratic story that does not count communal dates or anniversaries but, instead, focuses on the lived experience and the destiny of the individual. Verdecchia’s play has a peculiar political relevance in being conceived as a subjective inter-American history lesson on the issue of Latin diaspora in North America and, as such, presents an idiosyncratic history of a Canadian Latinx, created as a monologue reminding one of an oral storytelling of a destiny that is bound in the history web of the Americas.